Cosmopolitanism and Space in Kant’s Political Thought - Taraborrelli, Angela (Con-Textos Kantianos. International Journal of Philosophy, 2019)
Kant’s cosmopolitanism can be read from two main perspectives: temporal and spatial. Reading cosmopolitanism from a temporal perspective means paying attention to the historical realization of the ideal of cosmopolitanism and to its related issues such as: the progress of humankind, its final destination, the purpose of universal history, the highest purpose of nature. Instead, reading cosmopolitanism from a spatial perspective means paying attention, e.g. to the ‘fact’ of the sphericity of the earth and to its relationship with cosmopolitan right, territoriality, borders and freedom of movement. In this paper I would like to show how adopting a spatial perspective is useful not only in order to delimit a field of inquiry, but also to shed new light on apparently well-known and thoroughly investigated notions of Kant’s cosmopolitanism, such as the notions of the citizen of the world, of the cosmopolitan right, and of the World republic.
Keywords: Kant; Space; Cosmopolitan Right; Borders; World Republic